2014
DOI: 10.7785/tcrt.2012.500362
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Vector Mediated Delivery of RHBDD1 shRNA down Regulated the Proliferation of Human Glioblastoma Cells

Abstract: Abbreviation: RHBDD1: Rhomboid Domain Containing 1; shRNA: Short Hairpin RNAs; RNAi: RNA Interference.Rhomboid domain containing 1 (RHBDD1) gene, a new member of rhomboid family of proteins is highly responsible for the regulation of apoptosis by cleaving pro-apoptotic Bcl-2 family protein BIK. Therefore, the higher expression levels of RHBDD1 in cancer tissues may have a direct influence on cancer progression by arresting apoptosis. With this background this study was focused to find out the effect of RHBDD1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Using public microarray datasets, higher RHBDD1 expression in NSCLC patients had much shorter overall survival rates. Although RHBDD1 as a target gene by miRNAs was rarely reported in diseases, RHBDD1 has been frequently confirmed to be highly expressed in human cancers, such as colorectal cancer, glioblastoma, hepatocellular carcinoma, and chronic myeloid leukemia, whose knockdown inhibits the proliferation of these tumor cells [ 15 , 16 , 30 , 31 ]. Our data further demonstrated that RHBDD1 knockdown imitated, while overexpression reversed the effects of miR-924 on NSCLC cell proliferation, migration and invasion, as well as Wnt/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using public microarray datasets, higher RHBDD1 expression in NSCLC patients had much shorter overall survival rates. Although RHBDD1 as a target gene by miRNAs was rarely reported in diseases, RHBDD1 has been frequently confirmed to be highly expressed in human cancers, such as colorectal cancer, glioblastoma, hepatocellular carcinoma, and chronic myeloid leukemia, whose knockdown inhibits the proliferation of these tumor cells [ 15 , 16 , 30 , 31 ]. Our data further demonstrated that RHBDD1 knockdown imitated, while overexpression reversed the effects of miR-924 on NSCLC cell proliferation, migration and invasion, as well as Wnt/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Rhomboid domain-containing protein 1 (RHBDD1), a new member of the Rhomboid family is highly responsible for the regulation of apoptosis cleaving pro-apoptotic Bcl-2 family protein BIK [14]. Related studies showed that RNA interference (RNA) mediated RHBDD1 silencing significantly suppressed cell proliferation and cell cycle progression in hepatocellular carcinoma [15], glioblastoma [16] and colorectal cancer [17]. Moreover, Zhang et al [18] demonstrated that RHBDD1 could promote tumor metastasis by promoting Wnt/β-catenin signaling and epithelial-mesenchymal transition in colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence indicates that silencing RHBDD1 suppresses cell growth and proliferation in hepatocellular carcinoma [13], glioblastoma [14] and colorectal cancer [15]. In breast cancer [16,17] and colorectal cancer cells [18], RHBDD1 has been shown to promote migration, invasion and EMT.…”
Section: Introductionmentioning
confidence: 99%
“…RHBDD1 RNA and proteins are expressed in the human brain (Lonsdale et al, ; Uhlén et al, ). Moreover, this gene is implicated in many cancers including brain cancer (Miao et al, ; Wei, Lv, Chen, & Guan, ; Zhang, Zhao, et al, ; Zhang, Miao, et al, ). Nevertheless, currently, there are no studies reporting the role of RHBDD1 in neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%